Triaxial direct shear behavior and strength evaluation of granite under two high-temperature and stress-coupled conditions in deep underground openings - Binhui Liu; Zaobao Liu; Jianyu Xu; Liang Chen; Feng Tian; Biao Wang; Qiang Yang; Hongsu Ma (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The triaxial direct shear behavior of granite under high-temperature and stress-coupled conditions is critical for the safety evaluation of underground openings exposed to elevated temperatures, such as those in high-level radioactive waste disposal facilities. This study investigates the influence of thermal–mechanical coupling methods on the triaxial direct shear behavior of granite sourced from the Beishan Underground Research Laboratory in China by a self-developed triaxial direct shearing device. Two distinct thermal–mechanical loading paths were tested: (1) stress applied after temperature increase (SAT) and stress applied before temperature increase (SBT), with the latter simulating in situ host rock conditions. The results reveal that the peak direct shear strength of Beishan granite at a normal stress of 15 MPa decreased monotonically by approximately 5.45% as the temperature increased from room temperature to 150 °C under the SBT loading path. In contrast, under the SAT loading path, the peak strength initially increased by 28.5% from room temperature to 90 °C, followed by a subsequent decrease of 26.6% from 90 to 150 °C. These differences are attributed to the dual effects of thermal expansion in granite minerals, which are influenced by the temperature-stress coupling path. An integrated evaluation index M was developed to assess the granite strength evolution under high temperatures. When the evaluation index M > 5, the granite exhibits thermal strengthening; conversely, when M ≤ 5, the strength decreases in real-time high-temperature tests. These findings provide valuable insights for the stability assessment of engineering projects subjected to high stress and temperature conditions.